Methyl, Ethyl, and Propyl Nitrates: Global Distribution and Impacts on Reactive Nitrogen in Remote Marine Environments. Issue 21 (9th November 2018) - Fisher, Jenny A.; Atlas, Elliot L.; Barletta, Barbara; Meinardi, Simone; Blake, Donald R.; Thompson, Chelsea R.; Ryerson, Thomas B.; Peischl, Jeff; Tzompa‐Sosa, Zitely A.; Murray, Lee T.
Abstract: Alkyl nitrates (RONO2 ) are important components of tropospheric reactive nitrogen that serve as reservoirs for nitrogen oxides (NO x ≡ NO + NO2 ). Here we implement a new simulation of atmospheric methyl, ethyl, and propyl nitrate chemistry in a global chemical transport model (GEOS‐Chem). We show that the model can reproduce the spatial and seasonal variability seen in a 20‐year ensemble of airborne observations. Methyl nitrate accounts for 17 Gg N globally, with maxima over the tropical Pacific and Southern Ocean. Propyl nitrate is enhanced in continental boundary layers, but its global impact (6 Gg N) is limited by a short lifetime (8 days vs. 26 days for methyl nitrate and 14 days for ethyl nitrate) that inhibits long‐range transport. Ethyl nitrate has the smallest impact of the three species (4 Gg N). We find that methyl nitrate is the dominant form of reactive nitrogen (NO y ) in the Southern Ocean marine boundary layer, where its addition to the model corrects a large NO y underestimate in austral winter relative to recent aircraft data. RONO2 serve as a small net NO x source to the marine troposphere, except in the northern midlatitudes where the continental outflow is enriched in precursors that promote NO x loss via RONO2 formation. Recent growth in NO x emissions from East Asia has enhanced the role of RONO2 as a source of NO x to the remote free troposphere. This relationship implies projected future NO x emissions growth across the southern hemisphere may further enhance the importance of RONO2 as a NO x reservoir. Plain Language Summary: Nitrogen in the atmosphere has many impacts on atmospheric chemistry, including affecting how polluted the air is. Many nitrogen‐containing gases are released over polluted areas and are quickly broken down—staying far away from remote areas like the ocean. In this paper, we investigate a group of nitrogen gases (called alkyl nitrates ) that break down more slowly and so stay in the atmosphere long enough to be transported to the otherwise pollution‐free remote Pacific Ocean. These gases are also created naturally in the ocean and then make their way into the atmosphere, changing the atmospheric chemistry over the ocean. We use 20 years of measurements collected from aircraft, combined with a computer model, to determine the abundance and impacts of alkyl nitrates. We find that the smallest alkyl nitrates are particularly important over the Southern Ocean, where there are few other sources of nitrogen. We show that alkyl nitrates are playing an increasingly important role over the remote oceans because of recent growth in East Asian air pollution. This relationship implies that these gases may have a stronger influence on atmospheric chemistry over remote ocean areas in future if anticipated pollution growth in Africa, South America, and Southeast Asia is realised. Key Points: Model including air‐sea exchange reproduces observed alkyl nitrates from 20 years of airborne data Methyl nitrate is the dominant form of reactive nitrogen in the tropical Pacific and Southern Ocean Alkyl nitrates serve as a small but growing source of nitrogen oxides to the remote troposphere